Low temperature specific heat of Th-Gd spin glass - Sereni, J.G.; Huber, T.E.; Luengo, C.A.; Sereni, Julián (Elsevier, 1979)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina